2016
DOI: 10.1016/j.ejvs.2016.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Patient Specific Wall Stress Analysis and Mechanical Characterization of Abdominal Aortic Aneurysms Using 4D Ultrasound

Abstract: 4D ultrasound is applicable for wall stress analysis of AAAs, and offers the opportunity to perform wall stress analysis over time, also for AAAs who do not qualify for a CT or magnetic resonance imaging. Moreover, the patient specific material properties can be determined, which could possibly improve risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…Both proximal and distal ends were elongated to avoid the effects of the boundary conditions on the wall stresses in the aneurysm. 13 The CT based geometries were imported in the meshing software package 3-Matic 5.1 (Materialise, Leuven, Belgium) because of the complex meshing procedure around the bifurcation. Finally, the CT based meshes were created with mesh density similar to the US based mesh.…”
Section: Wall Stress Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Both proximal and distal ends were elongated to avoid the effects of the boundary conditions on the wall stresses in the aneurysm. 13 The CT based geometries were imported in the meshing software package 3-Matic 5.1 (Materialise, Leuven, Belgium) because of the complex meshing procedure around the bifurcation. Finally, the CT based meshes were created with mesh density similar to the US based mesh.…”
Section: Wall Stress Analysismentioning
confidence: 99%
“…In addition, manual segmentation of the US data was executed in the subgroup of AAA patients where no fusion was needed, since these data were similar to the 3D US data used in previous feasibility studies. 12,13 To compare the CT based geometries with the US contours, both modalities were registered using the described registration method. The agreement between the three different segmentations was quantified by the SI, a measure for agreement in geometry overlap, and the Hausdorff distance (HD), which quantifies the maximum local deviations between the two segmented geometries.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the large diameter criterion is found to be insufficient in predicting the risk of rupture and the necessity for surgical intervention . Biomechanical factors such as peak wall stress are found to be more reliable in predicting the risk of rupture than the size of aorta diameter . 4D phase‐encoding magnetic resonance imaging (MRI) which is used to evaluate blood flow characteristics showed that patient possessing ATAA exhibit disturbed flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have shown that, based on invivo data provided by medical images, these techniques can be used to estimate the in-vivo stress state of arterial segments in the presence of preloads [23,24,25], the unloaded configuration corresponding to those segments [8,26,27,28,29], or the material parameters characterizing the mechanical behavior of the soft tissues 1 Recoverable in the sense that the energy stored in the material can be fully recovered when kinematic restrictions are released, for example, through excision of the tissue. [30,31,32,33,34,35,36]. Remarkably, the predicted values for those material parameters are heavily influenced by the hypotheses considered to introduce the effect of residual stresses [37].…”
Section: Introductionmentioning
confidence: 99%